DEMAND TERHADAP PELAYANAN POLIKLINIK DI RUMAH SAKIT TK. II ISKANDAR MUDA BANDA ACEH - yanti fahmi; Aliamin Aliamin; Irwan Saputra (Fakultas Keperawatan-Universitas Syiah Kuala, 2021)
The growth of hospitals in Indonesia is currently very fast, this has resulted in competition between hospitals which has become increasingly fierce against public demand. One of the TNI-owned hospitals in Aceh Province is the Iskandar Muda TK.II Hospital, where currently the number of patient visits at the Iskandar Muda Kindergarten Polyclinic has decreased by around 4,634 in 2019. The purpose of this study is to find out more about demand. to services at the TK.II Iskandar Muda Hospital Banda Aceh polyclinic. The method in this study was an analytic survey with a cross sectional design, the number of samples in this study was 397 samples with accidental random sampling technique. The results of this study indicate that low demand (3 times) is 80.1% higher than the high demand (≥3 times) 19.9% at Iskandar Muda Kindergarten Hospital, Banda Aceh. The results of the bivariate analysis showed that the factors related to service demand in the polyclinic of Iskandar Muda Kindergarten Hospital Banda Aceh were BPJS PBI health insurance (OR = 2.9, 95% CI = 1.7-5.02, P-value = 0.0001), waiting time (OR = 2.3, 95% CI = 1.4-3.8, P-value 0.001), type of disease (OR = 5.4, 95% CI = 3.09-9 , 43, P-value = 0.0001), moderate disease severity (OR = 3.5, 95% CI = 1.8-6.7, P-value = 0.0001), severe disease severity (OR = 8.9, 95% CI = 3.9-20.3, P-value = 0.0001) and service quality (OR = 2.8, 95% CI = 1.5-5.3, P -value 0.001). The conclusion of this study is that health insurance, waiting time, type of patient disease, severity of disease and quality of service are factors related to service demand at the Polyclinic of Tk.II Iskandar Muda Hospital, Banda Aceh.